Feminist policy and platform economy: insights, methods and challenges - Sonia Ruiz García (Internet Policy Review)
This essay knits a dialogue between feminist political theory and feminist economy aiming at how to address the multiple challenges of platform economy nowadays. The essay’s purpose is to articulate perspectives and tools from feminist economic policy in order to generate a gender equal and intersectional platform economy. The essay first presents an overview of feminist political analysis and a theoretical evolution on feminist economics drawing on the notion of work, the working conditions, and the collective representation in the platform economy. Then it explores the aims and limits of feminist policy-making and economic feminist approaches—merged and transcended—focusing on governmental measures and feminist vindications. Third, the essay provides gender tools in the field of economic policy and outlines suggestions to favour a feminist path in the platform economy in the context of today’s complex environments.